2020
DOI: 10.1590/1678-4499.20190194
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest quality of ‘Brookfield’ apple field-treated with naphthalene acetic acid alone or combined with other growth regulators

Abstract: The Gala cultivars represent about 65% of the Brazilian apple production, however, it has a short harvest period, making necessary to use technologies that anticipate or delay fruit maturation. A widely used technology is the preharvest application of growth regulators. The objective of this investigation was to evaluate the effect of preharvest application of naphthalene acetic acid (NAA) combined with aminoethoxyvinylglycine (AVG) and 2-chloroethylphosphonic acid (Ethephon), on the quality of 'Brookfield' ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
(81 reference statements)
1
11
0
Order By: Relevance
“…Likewise, Ozturk et al (2015) found a reduction in the ethylene production rate in 'Jonagold' apple sprayed with AVG in single and split rates of 225 mL -1 . AVG blocks the production of 1-aminocyclopropane-1-carboxylate (ACC), by inhibiting its synthase, reducing the production of ethylene in the fruit (Wendt et al, 2020). However, ethephon, when releasing ethylene, promotes the autocatalytic production of this phytohormone (Steffens et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Ozturk et al (2015) found a reduction in the ethylene production rate in 'Jonagold' apple sprayed with AVG in single and split rates of 225 mL -1 . AVG blocks the production of 1-aminocyclopropane-1-carboxylate (ACC), by inhibiting its synthase, reducing the production of ethylene in the fruit (Wendt et al, 2020). However, ethephon, when releasing ethylene, promotes the autocatalytic production of this phytohormone (Steffens et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Scolaro et al (2015) and Yildiz et al (2012) also observed a higher flesh firmness in 'Royal Gala' and 'Red Chief' apples, respectively, that received a pre-harvest application of AVG, when compared with the control. The higher flesh firmness found in fruits sprayed with AVG may be related to the lower rates of ethylene production and respiration, as well as to the lower activity of ACC oxidase (Wendt et al, 2020). However, this variation in results between years of production may also be related to the stage of fruit maturation at harvest, fruit position on the canopy, and the different environmental conditions during the crop cycle (Drogoudi & Pantelidis, 2011;Zheng et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Anna apple fruit is a climacteric fruit, and a reduced in respiration is required to delay the climacteric peak in semi-arid regions (Abdel-Sattar and Kotb 2021). Previous studies have indicated that treating apple trees with 1-MCP or AVG before harvest with 30 days delays the climacteric peak of respiration and ethylene production during the ripening process, which extends the shelf life of climacteric fruits by delaying fruit ripening and senescence (Watkins 2006;Thongkum et al 2018;Lv et al 2020;Wendt et al 2020). Additionally, 1-MCP treatment that inhibits ethylene action may bene t fruit quality over an extended period after harvesting (Tomala et al 2020a).…”
Section: Marketabilitymentioning
confidence: 99%
“…MCP have been reported by previous studies to delay the synthesis of anthocyanins in the epidermis of Pink Lady(Whale et al 2008), Imperial Gala(Petri et al 2010), Royal Gala(Scolaro et al 2015), and Brook eld(Wendt et al 2020) apples because of the retarded development of red blush and reduced skin redness. In addition, when Brook eld apples were treated with NAA, the red color index was higher while it was lower with NAA + AVG treatment, and this delay the process of the skin color development to becomes red(Wendt et al 2020).…”
mentioning
confidence: 94%
See 1 more Smart Citation